2016
DOI: 10.3233/cbm-150564
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of plasma miRNA-718 for esophageal squamous cell carcinoma

Abstract: Plasma miRNA-718 is downregulated in ESCC patients and might serve as a potential diagnostic marker for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Moreover, upregulated miR-21 was detected in saliva supernatants with the AUC of 0.698 [48] and exosomes [49]. Not only miR-21, but also miR-23a [50], miR-506 [51], miR-718 [52] and miR-216a/b [53] were found as circulating biomarkers for diagnosis of ESCC. A meta-analysis [54] including 27 studies reported that circulating miRNAs with a combined AUC of 0.87 could be used as a biomarkers for early diagnosis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, upregulated miR-21 was detected in saliva supernatants with the AUC of 0.698 [48] and exosomes [49]. Not only miR-21, but also miR-23a [50], miR-506 [51], miR-718 [52] and miR-216a/b [53] were found as circulating biomarkers for diagnosis of ESCC. A meta-analysis [54] including 27 studies reported that circulating miRNAs with a combined AUC of 0.87 could be used as a biomarkers for early diagnosis of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence demonstrates that circulating miRNAs could serve as reliable biomarkers for the detection of various cancers. A research by Sun, Dong et al () has shown that the plasma miRNA‐718 expression level of patients with ESCC is significantly lower than that of healthy controls and that the plasma miRNA‐718 expression level is inversely correlated with the lymph node metastasis and TNM stage. Also, plasma miRNA‐718 might serve as a potential diagnostic marker for ESCC.…”
Section: Mirna As Biomarkers In Esophageal Cancermentioning
confidence: 99%
“…As a consequence, 22 articles (22,23,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) were eventually included in the meta-analysis. Among them, 7 articles (22,38,39,46,47,51,52) studied more than one miRNA. A total of 2 articles (34,44) focused on different miRNAs in the same subjects and contained a validation group.…”
Section: Characteristics Of the Studies Included In The Meta-analysismentioning
confidence: 99%